THE INFLUENCE OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE MEDIATED BY MOTIVATION AT ASTRA ISUZU MAKASSAR BRANCH - Manoppo, Claudia Darlen; Muis, Mahlia; Umar, Fauziah (Digital Economy and Digital Transformation Review, 2023)
This study is based on the fluctuation of company performance from 2018 to 2023. During the last six years, Astra Isuzu Makassar Branch has only achieved sales targets in 2021 and 2022. The leadership style at Astra Isuzu Makassar Branch is considered not yet strongly felt by employees because the leadership changes tend to be rapid, starting in 2018, there have been three changes of leaders. In 2019, when the leadership changed, there was turmoil within the branch so there was demotivation, which had an impact on the decline in branch performance. The purpose of this study was to determine (1) the influence of leadership style on employee performance, (2) leadership style on motivation, (3) motivation on employee performance, and (4) whether motivation can mediate leadership style on employee performance. This type of research is quantitative with acausal associative approaches. The sample consisted of 42 respondents with simple random sampling. Data collection was carried out using the questionnaire method and the data was analyzed using SEM-PLS. The results of the study show that (1) leadership style has a positive and significant influence on employee performance, (2) leadership style has a positive and significant influence on motivation, (3) motivation has a positive and significant influence on employee performance, and (4) a mediation analysis shows that motivation can mediate leadership style on performance.